Keynes and the British Humanist Tradition : the Moral Purpose of the Market. - Andrews, David (Routledge studies in the history of economics., 2010)
Looks at the relationship between the economics of John Maynard Keynes and the tradition of British Humanism, which dominated public life in the early years of the twentieth century. This book provides the reader with an understanding of Keynes and his core ideas, and is useful to students of economics.